Coping with the impacts of severe flood events in Dhaka’s slums – the role of social capital - Aßheuer, Tibor; Thiele-Eich, Insa; Braun, Boris (ERDKUNDE, 2013)
Slum dwellers are often exposed to natural hazards. While their high vulnerability seems to leave them unprotected to face these hazards, current research points to the fact that slum dwellers in particular are able to deal with crises remarkably well due to their high social capital. Using the example of extreme floods in the megacity Dhaka, we study the structure of social capital in slum dwellings by focusing on the question how this form of capital enables the management of these events. Three characteristics seem to be crucial for this: first, trusting relationships between the people, which allows for a quick and unbureaucratic way to receive financial aid in form of small credits. In addition, the multifaceted and redundant structures of social capital, which allow numerous people to ask for help from people in varying positions. The final characteristic consists of the various possibilities to resume work immediately after a flood event. However, while the social capital in Dhaka allows slum dwellers to overcome the crisis, it does not enable a long-term development. For the slum dwellers it is not sufficient to utilize social capital alone in order to become resilient in a comprehensive way.